Analysis of National Hoax Data for the Development of Digital Literacy in Indonesia: A Data-Driven Study and its Implications for Education Policy - Iin Syamsul Arifin; Nangkula Utaberta (Educia Journal, 2026)
The increasing use of digital media has facilitated information access while simultaneously accelerating the spread of hoaxes and misinformation. This study aims to analyze national hoax data in Indonesia and explore its implications for digital literacy development and education policy. Using a descriptive quantitative approach supported by content analysis, the study utilizes secondary data obtained from the official Komdigi hoax database. The data were analyzed through descriptive statistics, time-series analysis, and content analysis to identify dissemination patterns and content characteristics. The findings indicate that hoaxes remain a persistent feature of Indonesia’s digital information ecosystem and are commonly characterized by sensational narratives, emotional appeals, and pseudo-credible claims. The study argues that misinformation represents not only a communication challenge but also an educational and information management issue. Therefore, strengthening digital literacy is essential to enhance critical thinking, information verification, and responsible digital engagement. The findings suggest that digital literacy should be systematically integrated into educational policies and learning practices to foster more resilient and informed digital citizens.